2009
DOI: 10.3748/wjg.15.5224
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumor causing small bowelintussusception in a patient with Crohn’s disease

Abstract: We report a case of jejunoileal intussusception in a 42-year-old patient with Crohn's disease caused by a gastrointestinal stromal tumor. The patient complained of vague diffuse abdominal pain for a period of 4 mo. Intussusception was suspected at computer tomography and magnetic resonance imaging scans. Segmental resection of the small intestine was performed. Pathological examination of the surgical specimen revealed a gastrointestinal stromal tumor as well as aphthous ulcerations and areas of inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…but this case occurs in the same location, although studies have reported the possibility of GIST and in ammation being parallel to each other [14]. Theodoropoulos GE et al [15]reported that a patient with ulcerative colitis was diagnosed with GIST after surgery due to jejunoileum intussusception, but another study found that patients with in ammatory bowel disease (IBD) had an increased risk of cancer, especially it is for patients taking immunosuppressive agents [16]. Most cancers occur in the site of in ammation and have experienced the sequence of in ammationdysplasia-cancer [17,18].…”
Section: Discussionmentioning
confidence: 76%
“…but this case occurs in the same location, although studies have reported the possibility of GIST and in ammation being parallel to each other [14]. Theodoropoulos GE et al [15]reported that a patient with ulcerative colitis was diagnosed with GIST after surgery due to jejunoileum intussusception, but another study found that patients with in ammatory bowel disease (IBD) had an increased risk of cancer, especially it is for patients taking immunosuppressive agents [16]. Most cancers occur in the site of in ammation and have experienced the sequence of in ammationdysplasia-cancer [17,18].…”
Section: Discussionmentioning
confidence: 76%
“…Gastrointestinal stromal tumors are common in adults and may lead to intussusception [12,13]. Small tumor size (2 cm), low mitotic index, smooth muscle actin and S-100 positivity, poor C117 staining and CD10 negativity on immunohistochemical evaluation, low Ki-67 staining index (5%), and complete tumor resection are all indicators of good prognosis in the present case.…”
Section: Discussionmentioning
confidence: 86%
“…GISTs are rare clinical entities, constituting <3% of all gastrointestinal malignant neoplasms and represent only 20% of small-bowel malignant neoplasms (excluding lymphoma). [ 1 ]…”
Section: Discussionmentioning
confidence: 99%